Production method of superfine viscose staple fibers
By optimizing the spinning viscose pretreatment process and acid bath conditions, a spinneret hole structure suitable for ultrafine viscose fibers was designed, which solved the problem of inconsistent fineness of ultrafine fibers and thick cilia filaments in the existing technology, and achieved the density of monofilament wires High-quality ultrafine special viscose staple fibers from 0.4 to 0.44 dtex.
Patent Information
- Application Number
- CN202411280799.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, ultrafine fibers are not ultrafine viscose fibers in the strict sense, and the fineness range is relatively large, so problems such as coarse fibers or wool filaments are prone to occur during the production process.
By optimizing the spinning viscose pretreatment process and improving the acid bath conditions, designing a spinneret hole structure suitable for ultrafine viscose fibers, and adjusting the process parameters during impregnation, aging, yellowing and maturation, low-temperature vacuum defoaming and Negative drafting treatment ensures uniformity and fineness of spinning raw glue.
The production of ultrafine special viscose short fibers with a monofilament wire density of 0.4~0.44dtex is achieved, which reduces the impurity content and polymerization requirements, and improves the quality stability and fineness consistency of the fiber.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of ultrafine viscose staple fibers, and in particular to a method for producing ultrafine viscose fibers with a monofilament linear density of 0.4-0.44 dtex. Background Art
[0002] Ultrafine fibers have a large specific surface area, low bending stiffness, soft feel, smooth luster, good warmth retention and tightness, so they can be widely used in artificial leather, textiles, diaphragm materials, medical materials and other fields. They are favored by the international market for their unique functionality brought by their extraordinary fineness, silk-like appearance, good drape, good wearing comfort, and good natural texture in contact with the fiber surface. Viscose fiber, as a common regenerated cellulose fiber processed from natural plant-based fibers, is widely used in the field of textiles and clothing due to its excellent moisture absorption and breathability, softness, wearing comfort, dyeing performance, and high light resistance, heat and chemical reagent stability. However, the production of viscose fiber requires wet spinning, which has a long process and many process control points. The production of ultrafine viscose fiber is difficult. At present, most scholars and enterprises' inventions are concentrated in the field of ultrafine viscose fibers with a single-filament linear density ranging from 0.5 to 1.0 dtex. The production process and technology of ultrafine viscose fibers with a single-filament linear density of less than 0.5 dtex need to be further explored.
[0003] Ultrafine viscose fiber refers to a fiber with a fineness of less than 0.45 dtex. The fiber prepared in the prior art is not strictly ultrafine viscose fiber, and the fineness range spans a large range. The production of ultrafine fiber places higher requirements on pulp quality, with less impurity content, high polymerization degree requirements, and small colloid particles. In the production of ultrafine fibers, due to the small diameter of the spinneret hole, impurities such as elemental sulfur, zinc sulfide, zinc hydroxide, zinc trisulfide carbonate, and acid mud generated by the reaction are more likely to clog the spinneret hole, and at the same time flow on the surface of the spinneret to produce coarse fibers or hairy fibers. To this end, the present invention provides a method for producing ultrafine special viscose staple fibers by optimizing the spinning viscose pretreatment process, optimizing the spinneret structure, and improving the acid bath conditions. Summary of the invention
[0004] The purpose of the present invention is to provide a method for producing ultrafine viscose staple fibers, which solves the problem that ultrafine fibers in the prior art are not ultrafine viscose fibers in a strict sense and have a large fineness range.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] An ultrafine viscose staple fiber, with a single line density of 0.4-0.44 dtex, a length of 38-41 mm, a dry breaking strength of 2.16-2.48 cN / dtex, a wet breaking strength of 1.20-1.49 cN / dtex, a dry elongation of 18.21%, a whiteness of 80%-87%, and a defect of 0.4-0.6 mg / 100 g.
[0007] A method for producing ultra-fine viscose staple fibers, comprising the following steps:
[0008] (1) The natural cellulose pulp raw material is immersed in a sodium hydroxide solution to convert the cellulose into alkali cellulose, dissolve the hemicellulose, and reduce the degree of polymerization.
[0009] It should be noted that the sodium hydroxide solution is prepared from ion membrane caustic soda and water with a hardness of ≤0.2 degrees, has fewer impurities, and is used to soak the natural cellulose pulp raw material after being completely precipitated for a week to avoid the Ca 2 + Mg 2+ Impurities such as SiO2 react with acids to form insoluble salts that clog the nozzles.
[0010] (2) After the impregnation, the pulp is pressed to remove excess alkali solution, and then the blocky alkali cellulose is crushed on a pulverizer to become loose flocs, thereby increasing the surface area and facilitating the uniformity of subsequent chemical reactions. The cellulose is then transported to an aging drum for aging. After aging, the average degree of polymerization decreases. The aged flocs are then added to a xanthostat for xanthostat treatment. The xanthostat contains refined carbon sulfide that is colorless, transparent, oily, and has an evaporation residue of less than 0.01%. Cellulose xanthate is generated after xanthostat treatment. The feeding pipeline from the outlet of the aging drum to the inlet of the xanthostat is controlled at a low temperature of 10 to 20°C to reduce the temperature of the alkali cellulose and the initial temperature of xanthostating, thereby prolonging the xanthostating time, enhancing the uniformity of spinning glue generation, and reducing large-particle glue particles.
[0011] It should be noted that the use of refined carbon sulfide that is oily, colorless and transparent after distillation and has an evaporation residue of less than 0.01% can reduce the presence of harmful metal ions and impurities in the spinning rubber and ensure the quality of the finished fiber.
[0012] (3) Add cellulose xanthate and dilute alkali solution into a dissolver for dissolution, then send them into a grinding pump for grinding, and then send them into a mixer to obtain viscose. The viscose is placed for a period of time to fully mature to obtain spinning gum, ensuring its high maturity and low salt value. The maturity of the spinning gum is 9-15 mL (10% ammonium chloride) and the viscosity is (40±5) s.
[0013] It should be noted that a cold brine temperature regulating jacket is installed outside the dissolver and mixer. The temperature of the spinning rubber is lowered by continuously delivering cold brine to improve the dissolution effect. The rubber blocks and large particles are crushed and ground by a fine grinding pump, and the large particles are ground and cut into small particles to speed up the dissolution rate.
[0014] It should be noted that the above-mentioned maturity and viscosity can improve its spinnability, avoid problems such as roller wrapping, unstable forming, and thread breakage, and can also facilitate subsequent vacuum degassing and improve the degassing effect.
[0015] (4) Then, an alloy filter tube with a pore size of 6 microns is used to filter the spinning rubber before spinning to remove large-diameter particles. The filtered spinning rubber is then sent to a vacuum tank for degassing. The vacuum degree in the vacuum tank is 30 to 60 mbar and the temperature is 10 to 15°C.
[0016] It should be noted that filtration can further remove large-diameter particles, and vacuum degassing can remove tiny bubbles and reduce the probability of single-filament breakage.
[0017] (5) The spinning gum after filtering and degassing is spun into a coagulation bath, wherein the sulfuric acid concentration in the coagulation bath is 122-124 g / L, the zinc sulfate concentration is 7-8 g / L, the Berol Spin 653 dispersant is 3 g / L, the coagulation bath temperature is (50±2)°C, and the spinneret used for spinning includes a spinneret body and a plurality of spinneret holes opened on the spinneret body, the spinneret holes include a guide hole with a hyperbolic cross-section and a cylindrical hole, the narrow end of the hyperbolic guide hole is connected to the cylindrical hole, the spinneret hole (hyperbolic guide hole) inlet angle is 20°-25°, the spinneret aspect ratio (L / D) is 1.9, and the spinneret hole outlet aperture is 0.03 mm.
[0018] It should be noted that: the guide hole adopts a hyperbolic shape and the entrance angle is adjusted to 20°~25° to ensure that the energy of the spinning glue entering the capillary entrance of the spinneret is high, and at the same time, the curvature change when the guide hole is connected to the cylindrical hole is very small, which is conducive to the flow of liquid and can effectively prevent the disturbance of the liquid flow. The energy mutation can reach the minimum value or no mutation. The spinneret aperture is 0.03mm, which can ensure that the spinning glue stream coming out of the spinneret is thin enough. The spinneret aspect ratio is 1.9, which can ensure that the spinning liquid has a long distance constraint in the spinneret, forcing its macromolecules to be arranged in a better orientation, which is conducive to the formation stability of the stream. The spinneret aperture is reduced. In order to ensure the output, the number of spinnerets on a single-head spinneret is 3000. Preferably, the spinneret material is gold / platinum (60 / 40).
[0019] It should be noted that the addition of Berol Spin 653 dispersant in the above coagulation bath can effectively reduce the generation of sulfur and zinc sulfide in the acid bath, and at the same time suspend and disperse the products, improve the transparency of the acid bath, and reduce the blockage of the spinneret. The temperature of the coagulation bath can not only ensure that the orifice expansion rate is reduced, and the coarse fibers and strands caused by the adhesion of the filaments on the surface of the spinneret are reduced, but also reduce the formation speed when the temperature is too high, the forming speed is too fast, and the hydrogen sulfide and carbon disulfide gas escape in large quantities, which will cause a large number of pores in the fiber, and the strength and elongation of the finished fiber will decrease.
[0020] It should be noted that the diameter of the spinneret hole was reduced to 0.03 mm, and the number of spinneret holes was increased to 3000 to ensure production efficiency.
[0021] (6) When the spinning glue is ejected from the spinneret, it is first stretched at the nozzle, then stretched between the disks, and finally plasticized and drawn, with a stretching ratio of 60% and a shrinkage coefficient of 78%. After plasticization and drawing, a negative stretch of about 2% is taken before cutting to obtain ultrafine viscose fibers.
[0022] It should be noted that after the fiber is strongly stretched, the cellulose macromolecules are highly oriented, the internal stress of the fiber is large, the elasticity is poor, the hooking strength and elongation of the fiber are reduced, and a negative stretch of about 2% should be adopted before cutting after plasticization and stretching to allow the cellulose macromolecular chain segments to relax appropriately, improve the elasticity of the fiber, and increase the hooking strength and elongation.
[0023] (7) The ultrafine viscose fiber was cut into a common spinning length of 38 mm, washed with 80°C hot water, desulfurized with 85°C NaOH solution, bleached with pH=9 sodium hypochlorite solution, oiled and dried at low temperature for 72 hours to obtain ultrafine viscose fiber.
[0024] It should be noted that the acid discharge method in the coagulation bath is designed as a hole-type acid discharge, so that the acid bath flows in all directions when it is sprayed out, and the flow rate in a single direction is slowed down to reduce the impact on the wire strips and achieve stable acid supply.
[0025] The present invention removes large-diameter particles and easily precipitated impurities in the spinning rubber by adjusting the process parameters during the impregnation, aging, yellowing and ripening processes, and filtering and degassing after ripening, thereby ensuring that the diameter of the viscose particles meets the production requirements of ultrafine viscose fibers and avoiding the problems of broken yarns and unstable molding.
[0026] The present invention designs a spinneret that is more suitable for the production of ultrafine viscose fibers, reduces the radial expansion effect and the large degree of energy loss of the viscose fine flow at the spinneret outlet, thereby affecting the viscose spinnability. By reasonably designing the size, shape, number, angle control and drafting setting of the guide holes in the spinning spinneret, the continuity of the viscose fluid is maintained as much as possible on the basis of ensuring the fineness of the viscose fiber, and the production method does not affect its spinning efficiency.
[0027] Aiming at the characteristics that coarse fibers, parallel fibers and hairy fibers are easily produced in the spinning process of ultrafine fibers in the existing production process, the present invention improves the acid bath composition and conditions in the production process of ultrafine viscose fibers and improves the quality stability in the fiber production process.
[0028] The ultra-fine viscose staple fibers prepared by the present invention have a single-line density of 0.4-0.44 dtex, a smaller single-line density span, and higher fiber quality. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0030] Example 1
[0031] The present invention relates to a method for producing ultra-fine viscose staple fibers, comprising:
[0032] (1) Natural cellulose such as cotton linters and wood is used as pulp raw material. The raw material is impregnated with ion membrane NaOH with high purity after complete precipitation for one week and water with a hardness of 0.2. The impregnated raw material is pressed, crushed, and aged. It is yellowed with refined carbon sulfide with a colorless, transparent, oily state and an evaporation residue of less than 0.01% to generate cellulose xanthate. The cellulose xanthate and dilute alkali solution are added to a dissolver for dissolution, and then sent to a grinding pump for grinding. After grinding, it is sent to a mixer and left for 30 hours to obtain viscose with a maturity of 9 to 15 mL and a viscosity of (40±5) s.
[0033] (2) Use a 6-micron small-diameter alloy filter tube for pre-spinning filtration to remove large-diameter particles, and then send the filtered spinning raw rubber into a vacuum tank for degassing. The vacuum degree in the vacuum tank is 30-60 mbar and the temperature is 10-15°C.
[0034] (3) The spinneret uses a hyperbolic guide hole with an aspect ratio of 1.9, a spinneret hole diameter of 0.03 mm, and 3000 holes on a single spinneret.
[0035] (4) In the wire forming step, a large-sized acid bath was used for hole-type acid discharge, the sulfuric acid concentration was 122 g / L, the zinc sulfate concentration was 7.5 g / L, 3 g / L of Berol Spin 653 was added as a dispersant, and the coagulation bath temperature was (50 ± 2) °C.
[0036] (5) The stretching ratio is set to 60%, the shrinkage coefficient is set to 78%, and a 2% negative draft is set after plasticizing and stretching but before cutting.
[0037] (6) Post-treatment: The ultrafine viscose fiber was cut into a common spinning length of 38 mm, rinsed with 80°C hot water, desulfurized with 85°C NaOH solution, bleached with a pH 9 sodium hypochlorite solution, oiled and dried at low temperature for 72 hours to obtain ultrafine viscose fiber.
[0038] The ultrafine viscose fiber prepared in the example has a linear density of 0.4-0.44 dtex, a length of 38 mm, a dry breaking strength of 2.48 cN / dtex, a wet breaking strength of 1.49 cN / dtex, a dry elongation of 18.21%, a whiteness of 83%, and a defect of 0.4 mg / 100 g.
[0039] Example 2
[0040] The present invention relates to a method for producing ultra-fine viscose staple fibers, comprising:
[0041] (1) Cotton linters, wood, etc. are used as pulp raw materials, and ion membrane NaOH with high purity is selected. It is used after complete precipitation for one week, and water with a hardness of 0.2 is used to impregnate the raw materials. The impregnated raw materials are pressed, crushed, and aged, and are yellowed using refined carbon sulfide that is colorless, transparent, oily, and has an evaporation residue of less than 0.01% to generate cellulose xanthate. The cellulose xanthate and dilute alkali solution are added to a dissolver for dissolution, and then sent to a grinding pump for grinding treatment. After grinding, it is sent to a mixer and left for 48 hours to obtain viscose with a maturity of 13mL and a viscosity of 38s.
[0042] (2) Use a 6-micron small-diameter alloy filter tube for pre-spinning filtration to remove large-diameter particles, and then send the filtered spinning raw rubber into a vacuum tank for degassing. The vacuum degree in the vacuum tank is 30-60 mbar and the temperature is 10-15°C.
[0043] (3) The spinneret uses a hyperbolic guide hole with an aspect ratio of 1.9, a spinneret hole diameter of 0.03 mm, and 3000 holes on a single spinneret.
[0044] (4) The wire forming step uses a large-size acid bath tank for hole-type acid discharge, the sulfuric acid concentration is 124 g / L, the zinc sulfate concentration is 8 g / L, 3 g / L of Berol Spin 653 is added as a dispersant, and the coagulation bath temperature is 52°C.
[0045] (5) The stretching ratio is set to 60%, the shrinkage coefficient is set to 78%, and a 2% negative draft is set after plasticizing and stretching but before cutting.
[0046] (6) Post-treatment: The ultrafine viscose fiber was cut into a common spinning length of 41 mm, rinsed with 80°C hot water, desulfurized with 85°C NaOH solution, bleached with a pH 9 sodium hypochlorite solution, oiled and dried at low temperature for 72 hours to obtain ultrafine viscose fiber.
[0047] The ultrafine viscose fiber prepared in the example has a linear density of 0.4-0.44 dtex, a length of 41 mm, a dry breaking strength of 2.25 cN / dtex, a wet breaking strength of 1.37 cN / dtex, a dry elongation of 17.63%, a whiteness of 85%, and a defect of 0.6 mg / 100 g.
Claims
1. An ultra-fine viscose staple fiber, characterized in that: The single line density is 0.4-0.44dtex, the length is 38-41mm, the dry breaking strength is 2.16-2.48cN / dtex, the wet breaking strength is 1.20-1.49cN / dtex, the dry elongation is 18.21%, the whiteness is 80%-87%, and the defect is 0.4-0.6mg / 100g.
2. A method for producing the ultra-fine viscose staple fiber according to claim 1, characterized in that: The following steps are involved: (1) The natural cellulose pulp raw material is immersed in a sodium hydroxide solution to convert the cellulose into alkali cellulose, dissolve the hemicellulose, and reduce the degree of polymerization. The sodium hydroxide solution is prepared by ion membrane caustic soda and water with a hardness of ≤0.2 degrees; (2) After the impregnation, the pulp is subjected to a pressing process to remove excess alkali solution, and then the blocky alkali cellulose is crushed on a pulverizer to become loose flocs, and then the cellulose is transported to an aging drum for aging. After aging, the average degree of polymerization decreases, and then the aged flocs are added to a yellowing machine for yellowing treatment. The yellowing machine contains colorless, transparent, oily, and refined carbon sulfide with an evaporation residue of less than 0.01%. After yellowing, cellulose xanthate is generated, and the feeding pipeline from the outlet of the aging drum to the inlet of the yellowing machine is controlled at a low temperature of 10 to 20°C; (3) adding cellulose xanthate and dilute alkali solution into a dissolving machine for dissolution, and then sending them into a grinding pump for grinding treatment, and then sending them into a mixer to obtain viscose, and placing the viscose for a period of time to fully mature it to obtain spinning raw rubber, ensuring that it has high maturity and low salt value, and the maturity of the spinning raw rubber is 9-15mL, and the viscosity is 40±5s; (4) Then, an alloy filter tube with a pore size of 6 microns is used to filter the spinning rubber before spinning to remove large-diameter particles, and then the filtered spinning rubber is sent to a vacuum tank for degassing. The vacuum degree in the vacuum tank is 30 to 60 mbar and the temperature is 10 to 15° C.; (5) filtering and degassing the raw spinning gum to form a spinning agent through a coagulation bath, wherein the sulfuric acid concentration in the coagulation bath is 122-124 g / L, the zinc sulfate concentration is 7-8 g / L, the Berol Spin 653 dispersant is 3 g / L, the coagulation bath temperature is 50±2° C., the spinning spinneret includes a spinneret body and a plurality of spinneret holes opened on the spinneret body, the spinneret holes include a guide hole with a hyperbolic cross section and a cylindrical hole, the narrow end of the hyperbolic guide hole is connected to the cylindrical hole, the spinneret hole inlet angle is 20°-25°, the spinneret aspect ratio is 1.9, and the spinneret hole outlet aperture is 0.03 mm; (6) When the spinning glue is ejected from the spinneret, it is first stretched by the spinneret, then stretched between the disks, and finally plasticized and stretched, with a stretching ratio of 60% and a shrinkage coefficient of 78%. After plasticization and stretching, a negative stretch of about 2% is taken before cutting to obtain ultrafine viscose fibers; (7) The ultrafine viscose fiber was cut into a common spinning length of 38 mm, washed with 80°C hot water, desulfurized with 85°C NaOH solution, bleached, and dried to obtain the ultrafine special viscose fiber.
3. The method for producing ultra-fine viscose staple fibers according to claim 2, characterized in that: In step (3), a cold brine temperature regulating jacket is provided outside the dissolver and the mixer.
4. The method for producing ultra-fine viscose staple fibers according to claim 2, characterized in that: In step (5), the number of spinneret holes on the single-head spinneret is 3000.
5. The method for producing ultra-fine viscose staple fibers according to claim 2, characterized in that: The spinneret in step (5) is made of 60 / 40 gold / platinum.
6. The method for producing ultra-fine viscose staple fibers according to claim 2, characterized in that: In step (5), the acid discharge method in the coagulation bath is designed to be a hole-type acid discharge method.
Citation Information
Patent Citations
Production process of fine denier viscose staple fiber
CN103305939A
Superfine ultrashort viscose staple fiber for environment-friendly filtering material and preparation method thereof
CN103774262A
Flatting ultra-fine type high-strength and low-stretching viscose fibers and preparation method thereof
CN104911726A
Spinning jet special for cellulosic fibre spinning with solvent method
CN201195771Y
Spinning forming method for coloured flame-retardant viscose filaments and staple fibres without dyeing
WO2016184390A1
Cited By
Preparation method of high-water-absorption microporous regenerated cellulose fiber
CN120366910A